Kesalehan Digital (Analisis Fenomena Popularisasi Hadis Pada Status) - Inar; Juliana; Nurhayati, R.; Febrianty, Wita; Islamiah, Dina (Universitas Muhammadiyah Yogyakarta, 2022)
The birth of the tiktok application was based on an evolutionary process that occurred in the field of technology (digitalization) and internet innovation which led to the emergence of various types of social media. Indonesia In 2020, social media has experienced rapid development to become popular culture in Indonesia, namely the TikTok application, which has been downloaded 63.3 million times. Where the majority of users of this application are millennials, school age, or commonly known as generation Z. With a large number of users, the content offered to other users is also very diverse, but not many use it wisely so this can affect behavior and way of thinking. This study aims to describe forms of digital kesalehan and the factors that influence digital piety in the tiktok status of IAI Muhammadiyah Sinjai students. The type of research used is phenomenology with a qualitative research approach and the data collection techniques used are observation, interviews and documentation while the data analysis techniques used are data reduction, data presentation and drawing conclusions or verification. The results of this study are that the forms of digital kesalehan carried out by IAIM Sinjai students are very diverse, starting from making and sharing Islamic videos and increasing literacy about Islam by utilizing social media. But besides that, they apply the concept of preaching, namely Islamic teachings as the truth must be conveyed in a good and beautiful way so that what is conveyed can be accepted by the community and not vice versa. In addition, the factors that affect digital kesalehan in IAI Muhammadiyah Sinjai Student Tiktok Status come from internal and external factors where both are things that support a person in implementing what is called digital piety or good deeds done through social media